RATIONALITY IN SCIENCE: A COMPARISON STUDY BETWEEN IBNU RUSYD AND RENE DESCARTES - Nabila Huringiin; Sayyid Muhammad Indallah (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2022)
This article aims to compare the concept of rationality between Rene Descartes and Ibn Rushd. Namely Rene Descart who only uses reason or ratio, while Ibn Rushd who uses reason and revelation in reaching the ultimate truth. This article is a literature review where research data are taken from books and written sources that discuss the two figures. The method used in compiling this article is comparative descriptive with a philosophical approach. The results of this study conclude that the two concepts have something in common, namely the ratio or reason used to reach the truth. Even though they use the same ratio or reason, the main sources of knowledge between the two are very different. According to Rene Descartes, those who only use reason or reason will be able to reach the ultimate truth. Meanwhile, Ibn with his rationality based on revelation will reach the ultimate truth. Artikel ini bertujuan untuk membandingkan konsep rasionalitas antara Rene Descartes dan Ibnu Rusyd. Yaitu Rene Descart yang hanya menggunakan akal atau rasio, sedangkan Ibnu Rusyd yang menggunakan akal dan wahyu dalam mencapai kebenaran yang hakiki. Artikel ini adalah kajian pustaka dimana data penelitian diambil dari buku-buku dan sumber-sumber yang tertulis yang membahas antara kedua tokoh tersebut. Metode yang digunakan dalam menyusun artikel ini adalah deskriptif komparatif dengan pendekatan filosofis. Hasil dari kajian ini menyimpulkan, bahwasannya kedua konsep tersebut memiliki kesamaan yaitu pada rasio atau nalar yang digunakan untuk mencapai kebenaran tersebut. Meskipun menggunakan rasio atau nalar yang sama namun sember utama ilmu pengetahuan antara keduanya sangat berbeda. Menurut Rene Descartes yang hanya menggunakan akal atau rasio akan dapat mencapai kebenaran yang hakiki. Sedangkan Ibnu dengan rasionalitasnya dengan berlandaskan wahyu akan mencapai kebenaran hakiki.